Soil diversity influences on oil palm productivity in ultramafic ecosystems, Southeast Sulawesi, Indonesia - SYAMSU ALAM; Benito Heru Purwanto; EKO HANUDIN; EKA TARWACA SUSILA PUTRA (Society for Indonesian Biodiversity, 2020)
Abstract. Alam S, Purwanto BH, Hanudin E, Putra ETS. 2020. Soil diversity influences oil palm productivity in ultramafic ecosystems, Southeast Sulawesi, Indonesia. Biodiversitas 21: 5521-5530. Ultramafic is a unique ecosystem with an environmental gradient due to its high soil diversity. Understanding soil diversity in ultramafic ecosystems is fundamentally required to support sustainable agriculture management, particularly in oil palm plantation. This study investigated the relationship between soil diversity and productivity of oil palm in ultramafic ecosystems, Southeast Sulawesi. The soil survey has taken in Oheo, Langgikima, and Routa districts. Soil sample was collected from various toposequence, including upper, middle, and lower slope to describe soil properties, including soil texture, pH, CEC, SOC, TN, Av-P, Exc-K, Exc-Ca, and Exc-Mg. Whilst observation of oil palm productivity was done by recording the fresh-weight of fruit yield in hectare unit during a month. The results showed that the soil characteristics from the three sites were significantly different in soil texture, pH, CEC, Av-P, Exc-Ca, and Exc-Mg. A similar trend was also recorded in oil palm productivity wherein the highest oil palm productivity was discovered in Oheo (556.41+96.26 kg ha-1), followed by Langgikima (501.11+54.84 kg ha-1) and Routa (163.19+17.55 kg ha-1). Our study founded: pH, CEC, Av-P, Exc-K, Exc-Ca, and Exc-Mg significantly affected the productivity of oil palm. Based on these results, the soil diversity highly affected oil palm productivity in ultramafic ecosystems.